Desenvolvimento pós-embrionário do intestino anterior de Dermatobia hominis (Linnaeus Jr.) (Diptera, Cuterebridae) - Vieira, Ana Maria; Lello, Edy de [UNESP] (Sociedade Brasileira de Zoologia, 2001)
Foregut in D. hominis (Linnaeus Jr., 1781) as the majority of the larval Diptera somatic tissue, is made up of polytenic cells, and grows at the expenses of the polytenization of its nuclei followed by the increase in size of each cell. The oesophagus, of ectodermic origem, is interiorly covered by a chitinous squamous epithelium that rests upon a very thin basal lamina. This sheet is surrounded by thick muscle bundles. The oesophagus intussuscepts the midgut forming the cardia. The cardia, with three epithelial layers: two internal ones, of ectodermal origin and one external of endodermic origin. At the anterior portion of the cardia, between these two types of epithelium, there is a cluster of small, non polytenic cells, forming the imaginal disk of the foregut. Metamoiphosis begins at the end of the larval period with signs of nuclear degeneration of all the polytenic cells, as well as the increase in number of the imaginal disk ones. The oesophagic portion intussuscepted into the cardia, everts; its cells suffer apoptosis and are replaced by the new cells growing from the imaginal disk. The external layer cells also degenerate and are pinched off into the lumen of the very anterior portion of the midgut. The newly formed oesophagus intussuscepts de novo to form the two internal layers of the adult cardia. At the same time the midgut regenerative cells grow anteriorly to form the new external layer of the adult cardia.
Post-embryonic development of Dermatobia hominis (Linnaeus Jr.) (Diptera, Cuterebridae) foregut
Keywords: Diptera; Dermatobia hominis; foregut; cardia; metamoiphosis; histology; post-embryonic development